PENGARUH KUALITAS PELAYANAN, VARIASI PRODUK DAN PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN ULANG DI RESTORAN LAKOO BALI - Ni Putu Mira Khrisna Putri; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (EMAS, 2024)
A restaurant is a place that is organized commercially, which provides good service to consumers in the form of food and drinks so that consumers feel satisfied and will make repeat purchases. Apart from service quality, restaurants must also pay attention to the variety of products offered so that consumers are interested in visiting the restaurant. Apart from service quality and product variety, social media promotion is also very important in marketing in the restaurant sector because nowadays everything is digital so the reach of consumers is greater. . This research aims to examine the influence of service quality, product variety and social media promotions on repeat purchase decisions. The research was conducted at Lakoo Bali Restaurant. The sample from this research was 160 visitors who visited the restaurant. Sampling used non-probability sampling using the formula (5 x indicators). The method used is multiple linear regression analysis. The results of this research show that service quality has a positive and significant influence on repurchase decisions. Product variations have a positive and significant influence on repurchase decisions and social media promotions have a positive and significant influence on repurchase decisions.